Evaluasi Kinerja Sensor Penginderaan Jauh dalam Pemantauan Perubahan Iklim dan Dampaknya terhadap Keamanan Nasional - Maysuroh Lasmawati; Achmad Farid Wajdi; Dangan Waluyo (Mathematics Education Study Program, 2025)
The use of remote sensing techniques has been increased in Indonesia, given that this technique can obtain data and information without interacting directly with related objects, regions, and phenomena. This study then aims to analyze the performance of remote sensing sensors in Indonesia, especially in the monitoring of climate change and national security. The method used is a literature review method that focuses on the use of secondary data that includes trusted and credible textual materials. The study’s result shows that remote sensing has a crucial role in obtaining accurate data on climate change, thus disaster mitigation can be improved. Meteorological and climatological data provided by remote sensing sensors include cloud cover and movement, water vapor analysis, wind field analysis, surface radiation, atmospheric temperature structure, weather analysis and forecasting, and extreme weather estimation. Not only that, but remote sensing also plays an important role in supporting the realization of national security because of its ability to provide data on threats and security which is very useful in territorial guidance, military observation, and reconaissance activities.